Walkability Analysis in Kauman and Notoprayan Villages, Yogyakarta - Stefanus Christian Diyaneswara; Prisca Bicawasti Budi Sutanty; Rony Gunawan Sunaryo (Journal of Architectural Design and Urbanism, 2025)
This study evaluates the level of walkability in the Kauman and Notoprayan Villages in Yogyakarta to support connectivity between Ngabean parking facilities and major tourist destinations, such as Alun-Alun Utara and Kauman Mosque. The analysis employs six walkability variables: shaped, connected, comfortable, safety, security, and interesting. Data were collected through field observations, measurements, and documentation, and were then quantitatively analyzed using a scoring technique. The findings reveal that the average walkability index of the area is 3.58, indicating good walkability quality. The "shaped" variable recorded the highest score of 4.19, categorized as good. However, the "comfortable" variable received the lowest score of 2.96, reflecting the lack of supporting amenities such as shade, seating, and trash bins. Several outer roads require improvements in comfort, safety, and attractiveness. This research contributes significantly to urban kampung planning by providing design- and regulation-based recommendations to enhance the quality of pedestrian pathways, strengthen connectivity, and support a sustainable tourist experience.